2016
DOI: 10.1002/pssb.201552524
|View full text |Cite
|
Sign up to set email alerts
|

Formation of silicene on silver: Strong interaction between Ag and Si

Abstract: International audienceThe real-time formation of Si single layers on Ag(110) and Ag(111) has been investigated at different temperatures, by a combination of scanning tunnelling microscopy, grazing incidence X-ray diffraction, optical differential reflectance spectroscopy and density functional theory. It is shown that the reactivity of the Ag substrate with the Si atoms is important. The formation of Si nanoribbons on Ag(110) is accompanied by a missing-row reconstruction of the Ag surface, and the removed Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…A large number of simulated configurations have been found to have nearly the same free energy, the most stable one corresponding to the coincidence between a (√21×√21) R 10.9° silicene supercell and a (2√13×2√13) R 13.9° graphene supercell. Whereas such a variety of reconstructions are observed for Si/Ag(111), , all reconstructions observed on HOPG after Si evaporation correspond to (√3×√3) R 3 superstructures. Therefore, this superstructure is unlikely to be a silicene nanosheet weakly interacting with HOPG.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A large number of simulated configurations have been found to have nearly the same free energy, the most stable one corresponding to the coincidence between a (√21×√21) R 10.9° silicene supercell and a (2√13×2√13) R 13.9° graphene supercell. Whereas such a variety of reconstructions are observed for Si/Ag(111), , all reconstructions observed on HOPG after Si evaporation correspond to (√3×√3) R 3 superstructures. Therefore, this superstructure is unlikely to be a silicene nanosheet weakly interacting with HOPG.…”
Section: Resultsmentioning
confidence: 95%
“…But several studies had previously reported the formation of clusters instead of 2D sheets, indicating an island growth mode, also called Volmer–Weber. As the growth of silicene and germanene has been shown to occur in a narrow temperature window with a very small flux of Si or Ge atoms, ,, such specific growth conditions may not have been precisely considered in all studies. Moreover, as proposed in refs and , both monolayers and 3D islands could be present on the substrate surface.…”
mentioning
confidence: 99%
“…(√3×√3)R30° one at any realistic temperature. Despite all experimental efforts, however, it is only the (√3×√3)R30° configuration that always emerges with the HOPG substrate, whereas the expected variety of different reconstructions had been observed for the Si/Ag(111) system [16,17].…”
Section: Systemmentioning
confidence: 99%
“…Besides, it is not trivial to exclude formation of surface alloys between Si/Ge/Sn and a given metal substrate, which has even led to doubt the formation of silicene and germanene on metals. [126][127][128][129][130][131] In this context, successfully synthesizing these 2D materials on "nonmetals" would therefore represent a certain breakthrough in the field because these substrates are supposed to interact only weakly with the 2D ad-layer, hence preserving its intrinsic electronic properties. Therefore, in this review we have focused on the synthesis and characterization of silicene, germanene, and stanene on such materials.…”
Section: Outlook and Conclusionmentioning
confidence: 99%